All-solid-state Z-scheme system arrays of Fe2V4O13/RGO/CdS for visible light-driving photocatalytic CO2 reduction into renewable hydrocarbon fuel. Issue 4 (26th November 2014) - Li, Ping; Zhou, Yong; Li, Haijin; Xu, Qinfeng; Meng, Xiangguang; Wang, Xiaoyong; Xiao, Min; Zou, Zhigang
Abstract : An all-solid-state Z-scheme system array consisting of Fe2 V4 O13 /RGO/CdS was rationally designed for visible light-driving photocatalytic CO2 reduction into CH4 . Abstract : An all-solid-state Z-scheme system array consisting of an Fe2 V4 O13 nanoribbon (NR)/reduced graphene oxide (RGO)/CdS nanoparticle grown on the stainless-steel mesh was rationally designed for photoconversion of gaseous CO2 into renewable hydrocarbon fuels (methane: CH4 ).